Evaluation of some properties of heat curing denture base materials cured by different curing techniques - Bakr, Twana Omer; Ameen, Rizgar Mohammed (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Dry pressure curing device is one of the devices used in curing of acrylic resin denture bases. This study aimed to evaluate some properties of acrylic resins, cured by three different techniques. Methods: Two hundred and fifty two specimens were prepared from two brands of heat curing acrylic resin (Paladent20 and Major). The specimens were cured by three techniques (dry heat pressure curing, conventional curing and microwave irradiation). For each curing technique, seven specimens were prepared and some mechanical and physical properties were tested. Results: Less residual monomer showed in the dry heat pressure curing of Paladent 20 acrylic resin. The conventional curing of Major acrylic resin has shown the least porosity. The highest bending strength and less water sorption showed by microwave irradiation of Major acrylic resin specimens. Conclusion: Some properties of the specimens cured by the dry heat pressure curing device were better than other curing techniques. The microwave irradiation has some good properties when compared with other techniques. The Paladent 20 brand of acrylic resin showed better properties than the Major acrylic resin.